Aplikasi Pupuk N, P, K dan Konsorsium Pupuk Hayati terhadap Retensi Hara, Serapan, dan Hasil Kedelai (Glycine max (L.)) pada Inceptisol - Anni Yuniarti; Yuliati Machfud; Eso Solihin; Yogi Sudirman; Apong Sandrawati (Fakultas Pertanian Universitas Padjadjaran, 2018)
Inceptisol is a widespread soil order with low fertility. Hence it is necessary to improve its quality status through the application of chemical and biological fertilizers. The main objecttive of this study is to determine the effect of NPK fertilizer and biofertlizer consortia (BC) combinations in Inceptisols towards N and P availability in soil and uptake by soybean (Glycine max L.). Experiments were carried out from April to August 2016 at Ciparanje Experimental Farm, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, Sumedang at the approximate altitude of 720 meters above the sea level. Randomized Block Design experimental design consisted of ten treatments and three replications was used in this study. Treatments consisted of control (no treatment), Recommended NPK dosage, 0 NPK + 1 BC, ¼ NPK + 1 BC, ½ NPK + 1 BC, ¾ NPK + 1 BC, 1 NPK + 1 BC, ¾ NPK + ¼ BC, ¾ NPK + ½ BC and also ¾ NPK + ¾ BC. Experimental results showed that the combination of NPK fertilizer and soybean-spesific biofertilizer consortium increased soil total phosphate content, nitrogen uptake by plant, and soyben yield significantly. Keywords: Biofertilizer, Soybean, total-N, Uptake of N, Inceptisols